Synthesis and characterization of one-dimensional titanate structure - Ljubica M. Nikolić; Marija Maletin; Paula Ferreira; Paula M. Vilarinho (Processing and Application of Ceramics, 2008)
One-dimensional titania structures were synthesized trough a simple hydrothermal process in a highly alkaline conditions. The aim of this work was to elucidate the effect of time on the formation of 1D titanates as well on its structural characteristics (morphology, phase composition, surface area). Apart from that, the effect of heat treatment conditions on the stability of titanate based 1D samples has been investigated. The results have revealed that it is possible to form one-dimensional titanates already after 1 hour of hydrothermal synthesis. Although the composition of titanates is still under debate, the results probably correspond to the layered sodium titanates. The 1D prepared structures show a remarkable stability during heating, remaining the basic morphology and composition even up to 700°C.